Presidents, oligarchs and bureaucrats forms of rule in the post-Soviet space - Stewart, Susan (Ashgate, 2012)
Using case studies from the post-Soviet region, this title explores the character of post-Soviet regimes and reviews the political transformations they have experienced since the end of the Cold War. It highlights the difficulties and benefits of applying the concepts of hybrid regimes to the countries of the post-Soviet space.